Ответ:
Пошаговое объяснение:
x : 2,3=2,1 : 9 6/7
9 6/7х= 2,3 *2,1
69/7х= 4,83
69/7х= 4 83/100
69/7х= 483/100
х= 483/100 : 69/7
х= 483/100 * 7/69
х= 49/100
х= 0,49
х : 2,3 = 2,1 : 9. 6/7
х = 2,3 * 2,1 / 9. 6/7
х = 4,83/ 69/7
х = 483/100 * 7/69
х = 7/100 * 7/1
х = 49/100 или 0,49
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
x : 2,3=2,1 : 9 6/7
9 6/7х= 2,3 *2,1
69/7х= 4,83
69/7х= 4 83/100
69/7х= 483/100
х= 483/100 : 69/7
х= 483/100 * 7/69
х= 49/100
х= 0,49
Ответ:
Пошаговое объяснение:
х : 2,3 = 2,1 : 9. 6/7
х = 2,3 * 2,1 / 9. 6/7
х = 4,83/ 69/7
х = 483/100 * 7/69
х = 7/100 * 7/1
х = 49/100 или 0,49